Hubungan Antara Punca Tekanan Kerja Dan Tahap Perhubungan Perkahwinan - Rosfariza, Mohamed Ghani; Fatahyah, Yahya; Nur Fatihah, Mat Yusoff (Universiti Malaysia Sarawak, 2012)
The purpose of this study was to determine the relationship between the sources of job stress with the level of marital relationship. The sources of job stress were role overload, role insufficiency, role ambiguty, role boundary, responsibility and physical environment. As for the level of marital relationship, there were components such as task accomplishment, role perpormance, communication, affective expression, involvement, control and values and norms. There were two instrunents which had been used in this study. First is the Occupational Stress Inventory Revised Edition (OSI-R) (Occupational Role Questionaire)-ORQ which are used to measure the sources of job stress and the second is Family Assessment Measure Version 111 (Dyadic Relationship Scale. It is used to measure the level of marital relationship. There were 55 respondents among police officers from Ibu Pejabat Polis Kontigen (IPK) and Ibu Pejabat Polis Daerah (IPD) which were married at least two years and still living together. Result had shown the the number of children, role overload, role insufficiency, role ambiguty and responsibility had significant relationship with the level of marital relationship. Findings also showed that the sources of job stress had an inverse relationship with the level of marital relationship.